Penguatan Moral Melalui Pembelajaran PPKN di MIS Al-Afkari Kabupaten Deli Serdang - Abdulgani Jamora Nasution; Siskawati Ziliwu; Wildani Akhiriani; Almi Waina (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2023)
This research was conducted to discuss moral strengthening through Civics learning at MIS Al-Afkari, Deli Serdang Regency. School is an institution that educates students through teacher supervision. With moral strengthening through Civics learning in elementary schools, it is hoped that it will be able to shape the character of students in accordance with moral values ​​to become good, intelligent, skilled, and responsible citizens. The method used for this paper is descriptive qualitative. The results obtained from this research with the formation of the character of students and the attachment of moral values ​​to students are expected to be able to overcome the problems they face. And with this moral strengthening, so that the learning process can run effectively and efficiently, and can create citizens who love the Motherland and can play a role in building the Unitary State of the Republic of Indonesia. Keywords : Morals, Moral Education, Subjects Ppkn